2008
DOI: 10.1128/ec.00221-08
|View full text |Cite
|
Sign up to set email alerts
|

The Putative α-1,2-Mannosyltransferase AfMnt1 of the Opportunistic Fungal Pathogen Aspergillus fumigatus Is Required for Cell Wall Stability and Full Virulence

Abstract: Proteins entering the eukaryotic secretory pathway commonly are glycosylated. Important steps in this posttranslational modification are carried out by mannosyltransferases. In this study, we investigated the putative ␣-1,2-mannosyltransferase AfMnt1 of the human pathogenic mold Aspergillus fumigatus. AfMnt1 belongs to a family of enzymes that comprises nine members in Saccharomyces cerevisiae but only three in A. fumigatus. A ⌬afmnt1 mutant is viable and grows normally at 37°C, but its hyphal cell wall appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 36 publications
3
96
0
7
Order By: Relevance
“…The A. fumigatus genome contains a clear GDP-Man transporter homolog (AFUA_ 5G05740) whose importance is difficult to predict. It has recently been shown that protein O-mannosylation is dispensable in this fungus but is required for cell wall stability and full virulence (66,67). Yet the importance of N-glycan branching and elongation, and mannosylation of GIPCs, is currently undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…The A. fumigatus genome contains a clear GDP-Man transporter homolog (AFUA_ 5G05740) whose importance is difficult to predict. It has recently been shown that protein O-mannosylation is dispensable in this fungus but is required for cell wall stability and full virulence (66,67). Yet the importance of N-glycan branching and elongation, and mannosylation of GIPCs, is currently undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…pJW121 was constructed by cloning the tetracycline-dependent transactivator, the crgA terminator, and the tetO7::Pmin (a blunt-ended fragment derived from pVG2.2 after digestion with EcoRI and PmeI [22]) into the PmeI site of pSK379. pJW103 and pSK379 were described previously (7,23). Strains for the doxycycline-inducible expression of the C-terminally 6ϫHis-tagged full-length Rom2 and N-terminally hemagglutinin (HA)-tagged Rom2 with amino acids 733 to 1199 [HA-Rom2(733-1199)] were generated by PCR amplifying full-length Rom2 with primers Rom2-5g08550-fwd and His-Rom2-5g08550-rev and Rom2(733-1199) with the primers HA-Rom2GEF-5g08550-f and Rom2-5g08550-rev and cloning the respective PCR products in pSS005, yielding pSS006 and pSS009.…”
Section: G14vtetonmentioning
confidence: 99%
“…In addition, conidia are in contact with many different fungicidal factors present in the upper layer of the mucous epithelium. Among them, (Mellado et al 1996;Langfelder et al 1998;Tsai et al 1998;Mouyna et al 2005;Maubon et al 2006;Romano et al 2006;Li et al 2007;Schmalhorst et al 2008), signaling and metabolism regulation (Panepinto et al 2003;Krappmann et al 2004;Liebmann et al 2004;Fortwendel et al 2005Fortwendel et al , 2012Steinbach et al 2006;Zhao et al 2006;da Silva Ferreira et al 2007;Cramer et al 2008;Ibrahim-Granet et al 2008;Soriani et al 2008;Ejzykowicz et al 2009Ejzykowicz et al , 2010Gravelat et al 2010), thermotolerance (Bhabhra et al 2004;Wagener et al 2008), nutrition (Hensel et al 1998;Schrettl et al 2004Schrettl et al , 2007Hissen et al 2005;Moreno et al 2007;Liu et al 2010), toxin genes Sugui et al 2007;Spikes et al 2008), and response to stress (Paris et al 2003;Tsitsigiannis et al 2005;Reeves et al 2006;Willger et al 2008;Feng et al 2011;Dinamarco et al 2012;Grahl et al 2012). …”
Section: Pathogenesismentioning
confidence: 99%